ECONOMIC EVALUATION OF NEBULIZED MAGNESIUM SULPHATE IN ACUTE SEVERE ASTHMA IN CHILDREN. (14th November 2014) - Petrou, Stavros; Boland, Angela; Khan, Kamran; Powell, Colin; Kolamunnage-Dona, Ruwanthi; Lowe, John; Doull, Iolo; Hood, Kerry; Williamson, Paula
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: The aim of this study was to estimate the cost-effectiveness of nebulized magnesium sulphate (MgSO4) in acute asthma in children from the perspective of the UK National Health Service and personal social services. Methods: An economic evaluation was conducted based on evidence from a randomized placebo controlled multi-center trial of nebulized MgSO4 in severe acute asthma in children. Participants comprised 508 children aged 2–16 years presenting to an emergency department or a children's assessment unit with severe acute asthma across thirty hospitals in the United Kingdom. Children were randomly allocated to receive nebulized salbutamol and ipratropium bromide mixed with either 2.5 ml of isotonic MgSO4 or 2.5 ml of isotonic saline on three occasions at 20-min intervals. Cost-effectiveness outcomes were constructed around the Yung Asthma Severity Score (ASS) after 60 min of treatment; whilst cost-utility outcomes were constructed around the quality-adjusted life-year (QALY) metric. The nonparametric bootstrap method was used to present cost-effectiveness acceptability curves at alternative cost-effectiveness thresholds for either: (i) a unit reduction in ASS; or (ii) an additional QALY. Results: MgSO4 had a 75.1 percent probability of being cost-effective at a GBP 1, 000 (EUR 1, 148) per unit decrement in ASS threshold, an 88.0 percent probability of being more effective (in terms of reducing the ASS) and a 36.6 percent probability of being less costly. MgSO4 also had a 67.6 percent probability of being cost-effective at a GBP 20, 000 (EUR 22, 957) per QALY gained threshold, an 8.5 percent probability of being more effective (in terms of generating increased QALYs) and a 69.1 percent probability of being less costly. Sensitivity analyses showed that the results of the economic evaluation were particularly sensitive to the methods used for QALY estimation. Conclusions: The probability of cost-effectiveness of nebulized isotonic MgSO4, given as an adjuvant to standard treatment of severe acute asthma in children, is less than 70 percent across accepted cost-effectiveness thresholds for an additional QALY.